The eye as source of conceptual metaphors in Igbo (2024)
"This study examines how the eye (ányá) body part in Igbo is variously conceptualized and used metaphorically to express abstract concepts. Existing works on body part metaphors in Igbo were based on the traditionalist perspectives which sees metaphor as a rhetoric or figurative device with little attention from the conceptual metaphor perspective which sees metaphor as a systematic cognitive device used in the understanding of abstract concepts through the application of concrete ones. Data for this study were collected from 20 native speakers of Igbo through oral interview and observations and subjected to semantic analysis. It was discovered that the eye (ányá) body part is a source domain or concrete concept used in mapping out or expressing abstract concepts in Igbo such as intelligence, love, hope, time/distance, greed, among others. It was further discovered that metaphor is a powerful cognitive tool that help in expressing the Igbo worldviews which comprises of their culture, belief system, core values, and morals, among others. The study therefore concluded that the Igbo language is rich in the use of metaphors in everyday conversation and in expressing and understanding the worldviews of native speakers of the language.